L. Annaeus Seneca Troades : introduction, text, and commentary - Keulen, Atze J. (Mnemosyne, Supplements, 2001)
A.J. Keulen's new commentary on Seneca's Troades is the fruit of a lifetime devotion to this play. This extensive philological commentary on the Troades is a most welcome contribution to the study of Seneca's plays. Meaning, history and usage of Seneca's vocabulary are thoroughly discussed. The author provides ample comparison with Senecan prose and rival poets. In addition, the commentary addresses composition and word order, and discusses textual, metrical and grammatical difficulties. A full bibliography and three indices complete this valuable book.